Mechanistic understanding of pH effects on the oxygen evolution reaction. (10th February 2022) - Fornaciari, Julie C.; Weng, Lien-Chun; Alia, Shaun M.; Zhan, Cheng; Pham, Tuan Anh; Bell, Alexis T.; Ogitsu, Tadashi; Danilovic, Nemanja; Weber, Adam Z.
Abstract: The oxygen-evolution reaction (OER) is pivotal in many energy-conversion technologies as it is an important counter reaction to others that convert stable chemicals to higher-value products using electrochemistry. The local microenvironment and pH for the anode OER can vary from acidic to neutral to alkaline depending on the system being explored, making definitive mechanistic insights difficult. In this paper, we couple experiments, first-principles calculations based on density functional theory, microkinetics, and transport modeling to explore the entire pH range of the OER. At low current densities, neutral pH values unexpectedly perform better than the acidic and alkaline conditions, and this trend is reversed at higher current densities (> 20 mA cm −2 ). Using multiscale modeling, this switch is rationalized by a change from a dual-reaction mechanism to a single rate-determining step. The model also shows how the alkaline reaction rates dominate in the middle to high pH range. Furthermore, we explore that the local pH for near-neutral conditions is much different ( e.g ., 2.4 at the reaction surface vs. 9 in the bulk) than the pH extremes, demonstrating the criticality that transport phenomena plays in kinetic activity.